Conservation Agriculture: Making Climate Change Mitigation and Adaptation Real in Europe - González-Sánchez, E.J. (2017)
Agriculture and climate change are closely related. In this report, the European Conservation Agriculture Federation (ECAF) offers its experience and knowledge on how the agricultural sector can respond to climate change through Conservation Agriculture (CA). This experience is based on the development of several European (LIFE) public-funded projects based on the implementation of CA in Europe, and on a literature review on the topic. This document aims to serve as a basis for decision-making based on science and agricultural experimentation in Europe.